2023
DOI: 10.1186/s12870-023-04126-w
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of putrescine, salicylic acid, and ascorbic acid mitigates frost stress damage in Vitis vinifera cv. ‘Giziluzum’

Abstract: Background Cold stress is an effective factor in reducing production and injuring fruit trees. Various materials, such as salicylic acid, ascorbic acid, and putrescine, are used to alleviate the damage of abiotic stress. Results The effect of different treatments of putrescine, salicylic acid, and ascorbic acid on alleviating the damage of frost stress (− 3 °C) to grapes ‘Giziluzum’ was investigated. Frost stress increased the amount of H2O2, MDA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…The cold resistance of peach may be closely associated with multiple parameters. For instance, MDA, the end product of membrane lipid peroxidation, serves as a marker for assessing cell membrane damage in cold-resistance evaluations [ 15 , 16 ]. Under LT stress, plants accumulate various osmoregulatory substances to enhance their osmoregulation capacity and improve cold resistance [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cold resistance of peach may be closely associated with multiple parameters. For instance, MDA, the end product of membrane lipid peroxidation, serves as a marker for assessing cell membrane damage in cold-resistance evaluations [ 15 , 16 ]. Under LT stress, plants accumulate various osmoregulatory substances to enhance their osmoregulation capacity and improve cold resistance [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of grape response to drought, Zhao et al [ 23 ] found that exogenous Put could accelerate the ascorbate–glutathione (AsA-GSH) cycle and upregulate the transcription of PA synthesis genes and the accumulation of PAs, thereby improving the drought resistance of grapes. Jalili et al [ 24 ] found that the exogenous application of 5 mM Put could alleviate lipid peroxidation, increase membrane stability in grapes, and reduce frost damage in different grape varieties. However, few studies have investigated the effects of exogenous PAs on cold resistance in apples.…”
Section: Discussionmentioning
confidence: 99%
“…Although comparable studies on various plant species have been published with similar conclusions, the potential molecular mechanisms are different. For instance, previous studies demonstrated that the exogenous application of AsA enhanced cold stress tolerance by activating various antioxidant enzyme activities such as CAT, GPX, APX and SOD [ 46 ]. Other investigations, however, have reached different explanations.…”
Section: Discussionmentioning
confidence: 99%